Development Of High Performance And Low Cost Automatic Toll Payment System Using Rfid Technology For Malaysia Environment - Nik Azran , Ab Hadi (IJARET, 2014)
The proposed Automatic Toll Payment System is designed for efficient and convenient use of the public.The system is upgraded by using passive Radio Frequency Identification (RFID) technology instead of infrared that currently used nowadays to improve and make it low cost and have high performance toll payment system.A Malaysian toll payment system such as Touch n’ Go and SmartTag have the constraints that can lead to traffic congestion especially during the festival period.The RFID system uses tags that are mounted on the windshield of vehicles, through which information embedded in the tags are read by long read range RFID reader.The passive RFID technology is coming up with more advantages for public comfort.It is also less expensive since the passive RFID doesn’t use internal power supply to operate and it provides high speed detection. As vehicles don’t have to stop in a queue for making a payment,it assures time saving,fuel conservation, contributing in saving money, and at the same time reduced pollutions.Visual basic software is needed for implementation of the system for running the database of the entire system.The interface that has been designed,is used for output power and reading distance analysis before installation.The frequency analysis is carried out based on reading range from 1 meter to 5 meters for efficient speed detection. Every single frequency between 902.4 MHz to 927.8 MHz has been analyzed to gain efficiencies of tagging against the times.There are frequency band that cannot detect the transponder and vice versa.So the frequency configuration is important during installation for public convenience.